IDENTIFIKASI DISTRIBUSI SALURAN PEMASARAN KERIPIK TEMPE DI DESA PASIR AGUNG KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU (Studi Kasus Usaha Keripik Tempe Ibu Pur) - Rahim, Abdul (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
A good marketing product requires proper marketing distribution so that business can keep going and growing. Data collection method used was survey. The results showed that there are three marketing channels tempeh chips at the study site, the channel I: employers tempeh chips - mini market - consumers; II: businessman tempeh chips - shop - consumers; III: businessman tempeh chips - retailers - consumers. The level of efficiency of distribution channels marketing channels I and II is more efficient with a marketing margin of Rp 1,000 compared with the third marketing channel marketing margin of Rp 950.